The effect of caffeine supplementation on female volleyball players` performance and wellness during a regular training week - Siquier-Coll, J.; Delgado-García, G.; Soto-Méndez, F.; Liñán-González, A.; García, R.; González-Fernández, F. T. (Nutrients, 2024)
Background: caffeine is an ergogenic aid that still needs to be investigated in women`s sports performance. Methods: Eight semi-professional women`s volleyball players (height = 1.63 ± 0.08 m; weight = 66.67 ± 4.74 kg) voluntarily participated in this study. A randomized crossover design was implemented where players underwent caffeine and placebo conditions. In the caffeine condition, participants consumed 5 mg/kg of caffeine based on their body weight before acute training. The evaluations were performed over two weeks of training. In both conditions, the countermovement jump, repeated jumps for 15 s, and handgrip tests were performed. The change of direction was assessed using the 505 test. Well-being was also assessed with a wellness questionnaire. A repeated measures ANOVA and correlation analysis were performed. Results: The repeated measures ANOVA revealed a main effect of supplementation (F (1.7) = 8.41, p = 0.02, n^2 = 0.54) across the training week on physical performance. Additionally, there was a positive effect on perceived fatigue (F (1.7) = 7.29, p = 0.03, n^2 = 0.51). Conclusions: Caffeine improved performance and fatigue parameters over one week of training. Further research is needed on women, focusing on physical performance and wellbeing, especially during intense periods.